The limited feeding of tankage in the ration of fattening pigs when self-fed corn on alfalfa pasture. - Aubel, C.E. (Kansas Agricultural Experiment Station, 2012)
To produce swine profitably, it is necessary to make use of forage crops. This practice not only saves grain, but contributes to the general health of the hogs. Since swine feeders are seeking new and cheaper methods of producing hogs on pasture, the limited feeding of tankage for fattening pigs on alfalfa pasture was studied in this feeding trial.
Keywords: Swine; Tankage; Corn; Alfalfa pasture